Fire country. Season two [videorecording (DVD)] - Alejandro, Kevin, 1976-; Thieriot, Max; Burke, Billy; Farr, Diane, 1969- (CBS Studios, 2024)
Fire Country blazes back for a second season of death-defying action and searing drama. Bode is back behind bars and struggling with an immediate threat from the past when he learns a secret that could change everything. The atmosphere in his Northern California hometown of Edgewater is also heating up with family rivalries, a love triangle, and catastrophic natural disasters.